A new perspective: the common factors model as a foundation for social work practice education - Cameron, Mark; Keenan, Elizabeth King (Journal of Teaching in Social Work, 2009)
Foundation social work practice education is critical to the preparation of BSW practitioners for professional practice and the establishment of a theoretical and skill base upon which graduate students may build competencies in the advanced curriculum. Issues in the foundation practice curriculum may hinder this development. The common factors model holds promise as an organizing framework for foundation social work practice education. This model may help to resolve some key issues in social work and social work education, and may provide a useful, coherent, and empirical base for the foundation practice curriculum. © Taylor & Francis Group, LLC.
Keywords: Common factors; Direct practice; Foundation curriculum; Practice education; dept.swk; peer-reviewed

Teaching organization theory and practice: an experiential and reflective approach - Cameron, Mark; Turkiewicz, Rita M; Holdaway, Britt A; Bill, Jacqueline S; Goodman, Jessica; Bonner, Aisha; Daly, Stacey; Cohen, Michael D; Lorenz, Cassandra; Wilson, Paul R; Rusk, James (Journal of Teaching in Social Work, 2009)
The organization is often the overlooked level in social work's ecological perspective. However, organizational realities exert a profound influence on human development and well-being as well as the nature and quality of social work practice. This article describes a model of teaching organization theory and practice which requires master's social work students to assess their school of social work as well as their field placement agencies. Teaching organization theory and practice experientially may help students understand how organizations influence practice and empower them to see organization practice as a legitimate and important aspect of their work.
Keywords: Field education; Macro; Organization; Practice; Teaching; dept.swk; peer-reviewed